An Investigation Of Fundamental Motor Skills Underpinning The Sports Specific Skills Of Hockey For Ten Year Old Children. - Sprinkle, J.; Wilson, S.; Vine, K. (1997)
The research investigates the relationship between fundamental motor skills and sport specific skills for ten year old boys and girls within the context of hockey. Gender differences in baseline fundamental motor skills are explored and compared to the effects of instruction. The effect of instruction on either fundamental motor skills and hockey sport specific skill are determined by repeating the initial motor performance test which combines fundamental and sports specific skill items. The performances of seventy five children aged ten years are investigated through both process and product measures. The data was analysed using a repeated MANOVA which detects the levels of significance in the changes in skill level after intervention. Significant differences were detected in the pretest hockey hit and the two handed side arm strike, however, there were no significant differences on skill levels as a result of three diverse treatments. Comparisons are made between males and females in their initial skill levels and their relative changes in performance.